Laser-PSD based dynamic deflection monitoring of small- and medium-span beam bridges - Chen Xiong; Yingxiu Chen; Chengyu Cen; Yanmei Liang; Liu Mei; Qiling Luo; Wujian Long (Engineering Structures, 2026)

AMPK/mTOR/ULK1 signaling mediates ncoa4-dependent ferritinophagy in BPA-induced ferroptosis in HT-22 hippocampal neuronal cells - Yue Zhang; Yuxin Wang; Ping He; Qiling Liu; Haijun Han; Xuyuan Zhang; Chong Wang (Toxicology Letters, 2026)

Enhanced selective removal of ammonium nitrogen from wastewater by a modified chelating resin: Adsorption and regeneration mechanisms - Qing Xia; Chenbing Zhang; Xin Fang; Xiaodan Zhao; Shiji Liu; Qiling Yin; Zhen Zhou (Chemical Engineering Journal, 2026)

MoS2@Fe3O4 nanozyme redirects carbon to strengthen symbiotic nitrogen fixation in soybean for fertilizer-minimizing cleaner production - Kan Huang; Yining Liu; Youyou Zhao; Qingyun Xu; Chengxiao Hu; Qiling Tan; Songwei Wu; Sergey Shabala; Min Yu; Xuecheng Sun (Journal of Cleaner Production, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Role of NOX4 and GSH in Cadmium-Induced Renal Redox Homeostatic Dysregulation of Rats and APO Intervention Effect Study - Zhaofan Long; Langqiu Wei; Che Wang; Ningxi Wang; Li Song; Qiling Liu; Chuandao Shi (Biological Trace Element Research, 2026)

Transcriptomic reveals the acute exposure of ammonia nitrogen on muscle quality in fish: the coupling effect of acidity, thermal, and salinity - Ling Peng; Tao Yin; Shanbai Xiong; Juan You; Ru Liu; Qiling Huang; Soottawat Benjakul; Dan Jia (Aquaculture, 2026)

Superior ammonia nitrogen adsorption capacity and reusability biochar microsphere applied in live fish transportation - Ling Peng; Tao Yin; Zhiyong Song; Shanbai Xiong; Ru Liu; Juan You; Qiling Huang (Chemical Engineering Journal, 2025)

The carbon footprint and ecological costs of citrus production in China are going down - Jinye Li; Shanshan Liang; Xiaomin Liang; Xiaojuan Wang; Xinchen Bai; Yilin Chen; Kongjie Wu; Xiaoman Liu; Zhihao Dong; Qiling Tan; Xuecheng Sun; Chengxiao Hu; et al. (Journal of Cleaner Production, 2025)

Bisphenol A disrupts the neuronal F-actin cytoskeleton by activating the RhoA/ROCK/LIMK pathway in Neuro-2a cells - Yi Guo; Yuxin Wang; Qian Li; Qiling Liu; Xuyuan Zhang; Jiajia Ren; Chong Wang (Toxicology, 2024)

Combined dynamic transcriptome and flavonoid metabolome reveal the role of Mo nanoparticles in the nodulation process in soybean - Yining Liu; Songwei Wu; Xiaoming Qin; Min Yu; Sergey Shabala; Xiaomei Zheng; Chengxiao Hu; Qiling Tan; Shoujun Xu; Xuecheng Sun (Science of The Total Environment, 2024)

Nano molybdenum trioxide-mediated enhancement of soybean yield through improvement of rhizosphere soil molybdenum bioavailability for nitrogen-fixing microbial recruitment - Qibiao Li; Kan Huang; Zhichen Liu; Xiaoming Qin; Yining Liu; Qiling Tan; Chengxiao Hu; Xuecheng Sun (Science of The Total Environment, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

A mutant GH3 family β-glucosidase from Oenococcus oeni exhibits superior adaptation to wine stresses and potential for improving wine aroma and phenolic profiles - Yuzhu Zhao; Biying Zhang; Huawei Gu; Tongxin Xu; Qiling Chen; Jin Li; Penghui Zhou; Xueqiang Guan; Ling He; Yanying Liang; Kekun Zhang; Shuwen Liu; et al. (Food Microbiology, 2024)

Data driven multi-objective design for low-carbon self-compacting concrete considering durability - Boyuan Cheng; Liu Mei; Wu-Jian Long; Qiling Luo; Jinrui Zhang; Chen Xiong; Yuqing Shu; Zhangjian Li; Song Gao (Journal of Cleaner Production, 2024)

Adverse effects of bisphenol A and its analogues on male fertility: An epigenetic perspective - Xinyi Deng; Sihan Liang; Yuqian Tang; Yingxin Li; Ruijun Xu; Lu Luo; Qiling Wang; Xinzong Zhang; Yuewei Liu (Environmental Pollution, 2024)

Nuclei detection in breast histopathology images with iterative correction - Ziyi Liu; Yu Cai; Qiling Tang (Medical & Biological Engineering & Computing, 2024)

Transcriptomic-metabolomic analysis of magnesium-stimulated in peel coloration of Satsuma mandarin - Xiaoman Liu; Chengxiao Hu; Xiaodong Liu; Yuan Zhou; Qiling Tan; Xuecheng Sun; Songwei Wu (Postharvest Biology and Technology, 2023)

AI-guided design of low-carbon high-packing-density self-compacting concrete - Boyuan Cheng; Liu Mei; Wu-Jian Long; Shicong Kou; Qiling Luo; Yanjin Feng (Journal of Cleaner Production, 2023)

Heat wave exposure and semen quality in sperm donation volunteers: A retrospective longitudinal study in south China - Xinyi Deng; Qiling Wang; Chunxiang Shi; Jing Wei; Ziquan Lv; Suli Huang; Yong-Gang Duan; Xinzong Zhang; Yuewei Liu (Environmental Research, 2023)

Association between exposure to ambient air pollution and semen quality: A systematic review and meta-analysis - Ruijun Xu; Yanling Zhong; Rui Li; Yingxin Li; Zihua Zhong; Tingting Liu; Qiling Wang; Ziquan Lv; Suli Huang; Yong-Gang Duan; Xinzong Zhang; Yuewei Liu (Science of The Total Environment, 2023)

Prediction heavy metals accumulation risk in rice using machine learning and mapping pollution risk - Bing Zhao; Wenxuan Zhu; Shefeng Hao; Ming Hua; Qiling Liao; Yang Jing; Ling Liu; Xueyuan Gu (Journal of Hazardous Materials, 2023)

Exosomes Derived from Human Amniotic Mesenchymal Stem Cells Facilitate Diabetic Wound Healing by Angiogenesis and Enrich Multiple lncRNAs - Shangfeng Fu; Hongyan Zhang; Xiancai Li; Qiling Zhang; Chunyan Guo; Keqing Qiu; Junyun Feng; Xiaoxiao Liu; Dewu Liu (Tissue Engineering and Regenerative Medicine, 2023)

Illumination and regolith temperature at China’s next candidate lunar landing site Shackleton crater - Zhen Zhong; Jianguo Yan; Huaiyu He; Qiling Wen; Deyun Liu; Jean-Pierre Barriot (Science China Earth Sciences, 2023)

Effects of soil amendments on soil fertility and fruit yield through alterations in soil carbon fractions - Xiaomin Liang; Qin Chen; Muhammad Shoaib Rana; Zhihao Dong; XiaoDong Liu; Chengxiao Hu; Qiling Tan; Xiaohu Zhao; Xuecheng Sun; Songwei Wu (Journal of Soils and Sediments, 2021)

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

CRISPR/Cas9-mediated mutagenesis of Clpsk1 in watermelon to confer resistance to Fusarium oxysporum f.sp. niveum - Man Zhang; Qiling Liu; Xingping Yang; Jinhua Xu; Guang Liu; Xiefeng Yao; Runsheng Ren; Jian Xu; Lina Lou (Plant Cell Reports, 2020)

Interactive effects of molybdenum and phosphorus fertilizers on photosynthetic characteristics of seedlings and grain yield of Brassica napus - Hongen Liu; Chengxiao Hu; Xuecheng Sun; Qiling Tan; Zhaojun Nie; Xiaoming Hu (Plant and Soil, 2010)